The Evaluation of the Impact of Training as a Strategy of Improvement in the Organizations - José Tejada Fernández; Elena Ferrández Lafuente (Universidad Autónoma de Baja California, 2007)
The present article talks about the training impact evaluation as an improvement strategic in the organizations, so this evaluation allows to verify the quality of the training actions. So, training satisfies the necessities for what it is motivated and produces improvements as well as at the professional individual development as an improvement strategy. So, we start with an evaluation concept, their dimensions and indicators, inside a fragmented program evaluation conception; also, we consider the most usual problems that can appear in this evaluation process in key of resistances and facilitators. Finally, we show some improvement strategies.